Adaptation of straight pillars on implants with internal and external hexagonal connection by scanning electronic microscopy - Cerda Altamirano, José Paul (2020)
In oral implantology, the implant-pillar interface has been a subject of research and constant evolution, mainly from the biomechanical and biological point of view. Objective: To assess the gap in the implant-abutment interface in internal and external hexagonal connection implants by means of scanning electron microscopy (SEM). Materials and Methods: In vitro study in 24 implants (Bionnovation®) divided into two groups (n = 12): internal and external hexagonal connection. For the experiment, straight pillars with 30N of torque were screwed. In turn, 6 implants per group underwent 500,000 cycles of dynamic loading; Subsequently, the space of the pillar implant interface at 3 points of all samples was evaluated by MEB, the means of the results of each specimen were supported in Excel tables and analyzed in the BioEstat 5.3 program. Results: Using a T test for independent samples, with a significance of 95%, a very significant difference was found after the application of the dynamic load in the external hexagon implants (p = 0.0002). In the internal hexagon implants there was also a statistical difference (p = 0.03). Between the external and internal hexagon implants there were very significant differences in the accuracy of the adjustment in the abutment implant interface before and after the application of the dynamic loads (p = <0.0001 and p = 0.0003 respectively). Conclusions: Dynamic loads significantly increased the discrepancy in the implant-abutment connection of the external and internal hexagon implants (p = <0.05); additionally, the gap distance was greater for external hexagon implants in contrast to Internal Hexagon implants before and after dynamic loading, being very significant (p = <0.0003).